Literature as a lens for climate change using narratives to prepare the next generation - Young, Rebecca L. (Lexington Books, 2022)
"This collection offers practical approaches to using literature as a lens for teaching about climate change. Contributors share their classroom experiences and reflections to urge educators at all levels to prepare students for the challenges of a climate-changed world"--